President's Message - Knight, Mary (Operating Room Nurses Association of Canada Journal, 2002)
This issue of the Canadian Operating Room Nursing journal marks a major milestone - ORNAC has assumed ownership of the Journal, and has begun a relationship with our new publisher Clockwork Communications. The arrival of this Journal in your mailbox represents hours of work by the ORNAC Editorial Advisory Committee, chaired by Kim McLennan-Robbins of Alberta. Sincere thanks to everyone involved in making this issue a reality!